(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Tolstikh O. O. Specificity of future teacher’s professional training in the context of aesthetic education of elementary school students. The article describes the peculiarities of the aesthetic education in primary school and proves their influence on the elementary school teacher professional training in work with the pupils of this age category.